Preparation method of metal particles with hollow structures

By simplifying the template construction and removal process, combined with the metal precursor reaction and reduction process, the problems of cumbersome preparation process and uncontrollable morphology in the existing hollow structure metal particle material preparation methods are solved, and hollow metal particles with regular shape and uniform particle size are prepared, which is suitable for industrial production.

CN119703105APending Publication Date: 2025-03-28GUANGXI UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202311277387.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-28
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing preparation methods for hollow structure metal particles have problems such as cumbersome preparation process, complex template construction, difficult template removal and uncontrollable sample morphology.

Method used

A new preparation method is adopted to form a water-soluble salt or alkali template by mixing a soluble salt or alkaline with a surface modifier, and then react with a metal precursor to obtain hollow structural metal particles through a reduction process. This method simplifies the template construction and removal process, improves the regularity of particle morphology and uniformity of particle size distribution.

Benefits of technology

The preparation of hollow metal particles with regular morphology and uniform particle size is achieved, which simplifies the preparation process, reduces costs, and increases yield, making this method suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119703105A_ABST
    Figure CN119703105A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of metal particles with hollow structures, which comprises the following steps: mixing a soluble salt solution or a soluble alkali solution with a corresponding poor solvent at a certain temperature according to a certain proportion to obtain a water-soluble salt or alkali template; dissolving a metal precursor and a surfactant in corresponding solvents, and adding the solvents into the template solution in proportion to react for sufficient time; washing to remove the residual metal precursor in the sample, re-dispersing in the solvent, and adding a reducing agent for reaction; and washing with water to remove the water-soluble template to obtain the hollow metal particles. In the template construction stage, the template with more regular morphology and more uniform particle size distribution can be simply and quickly obtained; in the hollow metal preparation stage, particle damage and agglomeration and generation of solid particles can be effectively reduced; in the template removal stage, the template can be removed more simply, conveniently and safely. The hollow metal particles prepared through the method are regular in morphology, and the particle diameter ranges from 50 nm to 10 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal particle preparation, and more specifically, to a method for preparing hollow structure metal particles. Background Art

[0002] Hollow structured metal particles have unique structural advantages, making them more widely used in many fields compared to solid metal particle materials.

[0003] In the field of catalysis, hollow-structured metal materials provide additional contact sites due to their increased specific surface area, thereby greatly improving the catalytic advantage [Huang K, Sun Y, Zhang Y, et al. Hollow-structured metaloxides as oxygen-related catalysts[J]. Advanced Materials, 2019, 31(38): 1801430.].

[0004] Kim's team prepared hollow Pt / Ag composite nanospheres with highly enhanced catalytic properties through galvanic replacement reaction, and found that hollow Pt / Ag composite nanostructures can effectively catalyze the degradation of rhodamine B in the presence of potassium borohydride [Kim MR, Lee DK, Jang D J. Facile fabrication of hollow Pt / Ag nanocomposites having enhanced catalytic properties [J]. Applied Catalysis B: Environmental, 2011, 103 (1-2): 253-260.].

[0005] Zhang et al. used etching method to synthesize hierarchical Fe3O4@MnO2 hollow spheres and used them for catalytic degradation of high-concentration pollutants [Zhang S, Fan Q, Gao H, et al. Retracted Article: Formation of Fe3O4@MnO2ball-in-ball hollow spheres as a high-performance catalyst with enhanced catalytic performances[J]. Journal of Materials Chemistry A, 2016, 4(4): 1414-1422.].

[0006] In terms of battery energy storage, the cavities of hollow structured metal particle materials provide abundant electrochemical active sites and large electrolyte-electrode contact area for rapid diffusion and reaction. In addition, the cavities can effectively prevent the aggregation of encapsulated electroactive nanoparticles and adapt to the significant volume changes accompanying repeated charge / discharge processes [Xie XC, Huang KJ, WuX. Metal-organic framework derived hollow materials for electrochemical energy storage [J]. Journal of Materials Chemistry A, 2018, 6 (16): 6754-6771.].

[0007] Shen et al. developed a new and universally applicable strategy for the synthesis of NiCo2O4 hollow spheres as advanced electrode materials for lithium-ion batteries and supercapacitors with excellent electrochemical performance [Shen L, Yu L, Yu XY, et al. Self-templated formation of uniform NiCo2O4 hollow spheres with complex interior structures for lithium-ion batteries and supercapacitors[J]. Angewandte chemie international edition, 2015, 54(6): 1868-1872.].

[0008] Yu's team developed a method for growing hollow transition metal (Fe, Co or Ni) oxide nanoparticles on graphene sheets. When used as the negative electrode of lithium-ion batteries, they exhibit excellent electrochemical performance, with high reversible capacity and stability at high current density [Yu X, Qu B, Zhao Y, et al. Growth of hollow transition metal (Fe, Co, Ni) oxide nanoparticles on graphene sheets through Kirkendall effect as anodes for high-performance lithium-ion batteries [J]. Chemistry–A European Journal, 2016, 22 (5): 1638-1645.].

[0009] In electromagnetism, the cavity of the hollow structured metal particle material causes electromagnetic waves to reflect multiple times inside, thereby converting the electromagnetic waves into heat energy and consuming it [Zheng X, Zhang H, Jiang R, et al. Lightweight polyurethane composite foam for electromagnetic interference shielding with high absorption characteristic [J]. Journal of Colloid and Interface Science, 2023.].

[0010] Ma prepared a porous CuO / carbon composite material by impregnating nitrate into a MOF template. At 14.9 GHz with a matching thickness of 1.55 mm, an optimal reflection loss (RL) of -57.5 dB was obtained, and an RL value of less than -10 dB was obtained in the range of 13–17.7 GHz [Ma J, Zhang X, Liu W, et al. Direct synthesis of MOF-derived nanoporous CuO / carbon composites for high impedance matching and advanced microwave absorption [J]. Journal of Materials Chemistry C, 2016, 4 (48): 11419-11426.].

[0011] Ouyang's team used FeCoNi-based MOF as a precursor and obtained hollow spherical trimetallic FeCoNi@C microwave absorption materials through high-temperature carbonization. The RL value reached -64.75dB at 15.44GHz [Ouyang J, He Z, Zhang Y, et al. Trimetallic FeCoNi@C nanocomposite hollow spheres derived from metal–organic frameworks with superior electromagnetic wave absorption ability [J]. ACS applied materials & interfaces, 2019, 11 (42): 39304-39314.].

[0012] However, the current preparation methods of hollow structured metal particle materials still have the following problems: 1) the preparation process is relatively cumbersome; 2) the template construction is relatively complex; 3) it is relatively difficult to remove the template; 4) the sample morphology is relatively uncontrollable. Summary of the invention

[0013] The technical problem to be solved by the present invention is to provide a method for preparing hollow structured metal particles. In the template construction stage, the preparation method can simply and quickly obtain a template with a more regular morphology and a more uniform particle size distribution; in the hollow metal particle preparation stage, it can effectively reduce particle breakage and agglomeration and the generation of solid particles; in the template removal stage, the template can be removed more simply and safely. The hollow metal particles prepared by the preparation method have a regular morphology and a particle diameter of 50nm-10μm.

[0014] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0015] A method for preparing hollow structure metal particles comprises the following steps:

[0016] 1) dissolving a soluble salt or soluble base in a good solvent to obtain a soluble salt or soluble base solution; dissolving a surface modifier in a poor solvent for the soluble salt or soluble base to obtain an anti-solvent for the corresponding soluble salt or soluble base;

[0017] 2) heating or freezing the soluble salt or soluble alkali solution and the anti-solvent respectively, and then stirring or ultrasonically mixing them in proportion to obtain a water-soluble salt or alkali template;

[0018] 3) dissolving the metal precursor and the surface modifier in a corresponding poor solvent of a soluble salt or a soluble base, and mixing them with a water-soluble salt or base template in proportion, stirring the reaction continuously, and washing by centrifugation to obtain hollow metal salt particles;

[0019] 4) dispersing the metal salt particles obtained in step 3) in a solvent, adding a reducing agent to carry out a reduction reaction under temperature-controlled stirring conditions to obtain a hollow metal particle suspension, centrifugally separating and washing to obtain hollow structure metal particles.

[0020] As an embodiment, in step 1), the soluble salt or soluble base is selected from one of the following substances: sodium chloride, sodium carbonate, sodium citrate, sodium sulfate, sodium nitrate, sodium hydroxide, potassium chloride, potassium carbonate, potassium citrate, potassium sulfate, potassium nitrate, potassium hydroxide.

[0021] As an embodiment, in step 1), the good solvent for the soluble salt or soluble base is selected from one or more of the following substances: deionized water, glycerol, ethylene glycol, and methanol.

[0022] As an embodiment, in step 1), the surface modifier is selected from one or more of the following substances: hexadecyltrimethylammonium bromide, polyvinyl pyrrolidone, polyethylene glycol, sodium dodecyl sulfonate, sodium dodecyl sulfate, Tween 80, and silane coupling agent.

[0023] As an embodiment, in step 1), the poor solvent for the soluble salt or soluble base is selected from one or more of the following substances: ethanol, isopropanol, n-butanol, acetone, acetonitrile, tetrahydrofuran.

[0024] As an embodiment, in step 1), the amount of the soluble salt or soluble base is 0.1wt%-saturation of the total mass of the good solvent; more preferably, the amount of the soluble salt or soluble base is 1wt%-saturation of the total mass of the good solvent.

[0025] As an embodiment, in step 1), the amount of the surface modifier used is 0.1-2 wt% of the total mass of the poor solvent; more preferably, the amount of the surface modifier used is 0.1-1 wt% of the total mass of the poor solvent.

[0026] As an embodiment, in step 2), the soluble salt or soluble alkali solution is heated to a temperature of 0-200°C before mixing with the anti-solvent; more preferably, the soluble salt or soluble alkali solution is heated to a temperature of 50-100°C before mixing with the anti-solvent.

[0027] As an embodiment, in step 2), the temperature of the anti-solvent before mixing is -20-60°C; more preferably, the temperature of the anti-solvent before mixing is -10-25°C.

[0028] As an embodiment, in step 2), the volume ratio of the soluble salt or soluble alkali solution and its anti-solvent is 1:5-1:200; more preferably, the volume ratio of the soluble salt or soluble alkali solution and its anti-solvent is 1:20-1:100.

[0029] As an embodiment, in step 2), the stirring rate is 300-2400 rpm; more preferably, the stirring rate is 600-1800 rpm.

[0030] As an embodiment, in step 2), the ultrasonic power is 10-600W; more preferably, the ultrasonic power is 100-600W.

[0031] As an embodiment, in step 2), the stirring or ultrasonic time is 1-30min; more preferably, the stirring or ultrasonic time is 2-15min.

[0032] As an embodiment, in step 3), the metal precursor is selected from one or more of the following substances: silver nitrate, tetrachloroauric acid, copper sulfate, copper nitrate, ferric chloride, barium sulfate, barium chloride, cobalt chloride, and nickel chloride.

[0033] As an embodiment, in step 3), the surfactant is selected from one or more of the following substances: polyvinyl pyrrolidone, polyethylene glycol, silane coupling agent, hexadecyltrimethylammonium bromide, Tween 80.

[0034] As an embodiment, in step 3), the amount of the metal precursor used is 0.1-10 wt % of the total mass of the poor solvent; more preferably, the amount of the metal precursor used is 1-5 wt % of the total mass of the poor solvent.

[0035] As an embodiment, in step 3), the amount of the surface modifier used is 0.1-10 wt % of the total mass of the poor solvent; more preferably, the amount of the surface modifier used is 1-5 wt % of the total mass of the poor solvent.

[0036] As an embodiment, in step 3), the ratio of the metal precursor solution to the water-soluble template solution is 1:1-1:20; more preferably, the volume ratio of the metal precursor solution to the water-soluble salt or base template solution is 1:1-1:10.

[0037] As an embodiment, in step 3), the mixing and stirring time of the metal precursor solution and the water-soluble salt or base template solution is 1-96 hours; more preferably, the mixing and stirring time of the metal precursor solution and the water-soluble salt or base template solution is 24-72 hours.

[0038] As an embodiment, in step 3), the metal precursor solution and the water-soluble salt or base template solution are mixed and stirred at a temperature of -20-60°C; more preferably, the metal precursor solution and the water-soluble salt or base template solution are mixed and stirred at a temperature of -10-25°C.

[0039] As an embodiment, in step 4), the solvent is selected from one or more of the following substances: ethanol, isopropanol, n-butanol, acetone, acetonitrile, tetrahydrofuran, deionized water, glycerol, ethylene glycol, and methanol.

[0040] As an embodiment, in step 4), the reducing agent is selected from one or more of the following substances: hydrazine hydrate, sodium citrate, ascorbic acid, sodium borohydride, and ethylene glycol.

[0041] As an embodiment, in step 4), the reduction reaction time is 1 min-6 h; more preferably, the reduction reaction time is 10 min-1 h.

[0042] As an embodiment, in step 4), the temperature of the temperature-controlled stirring is -20-60°C; more preferably, the temperature of the temperature-controlled stirring is -10-25°C.

[0043] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0044] Unless otherwise specified, all raw materials in the present invention can be purchased from the market, and the equipment used in the present invention can adopt conventional equipment in the relevant field or refer to the existing technology in the relevant field.

[0045] Compared with the prior art, the present invention has the following beneficial effects: :

[0046] 1) The soluble salt template prepared by the present invention has a small and uniform particle size of 200nm-3μm, its morphology can be controlled, and the template preparation time is greatly shortened;

[0047] 2) The present invention can flexibly control the size and wall thickness of the hollow metal particles by changing the particle size of the template particles, the reaction solution, the reaction time, etc., so as to achieve the performance of absorbing electromagnetic waves of different bands;

[0048] 3) The hollow metal particles prepared by the present invention have a stable morphology, ≥99% of the hollow metal particles are regular, and the particle size is between 50nm-10μm;

[0049] 4) The preparation method of the hollow structure metal particles of the present invention has higher yield, low cost, low biological toxicity, simple operation, and is easy to industrialize. Compared with the traditional template, the template removal method is simple and fast and does not produce secondary pollution. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The specific embodiments of the present invention will be further described in detail below with reference to the accompanying drawings.

[0051] Figure 1 This is a scanning electron microscope image of the molten salt template prepared in Example 1;

[0052] Figure 2 This is a scanning electron microscope image of the hollow structure silver particles prepared in Example 1;

[0053] Figure 3 This is a scanning electron microscope image of the dissolved salt template prepared in Comparative Example 1;

[0054] Figure 4 This is a scanning electron microscope image of the dissolved salt template prepared in Comparative Example 2;

[0055] Figure 5 This is a scanning electron microscope image of the dissolved salt template prepared in Comparative Example 3;

[0056] Figure 6 This is a scanning electron microscope image of the dissolved salt template prepared in Comparative Example 4;

[0057] Figure 7 This is a scanning electron microscope image of the hollow structure silver particles prepared in Comparative Example 5;

[0058] Figure 8 This is a scanning electron microscope image of the hollow structure silver particles prepared in Comparative Example 6;

[0059] Fig. 9 This is a scanning electron microscope image of the hollow structure silver particles prepared in Comparative Example 7. DETAILED DESCRIPTION

[0060] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and accompanying drawings. Similar components in the accompanying drawings are represented by the same reference numerals. It should be understood by those skilled in the art that the content specifically described below is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0061] Various cross-sectional views of the embodiments disclosed in the present invention are shown in the accompanying drawings. These drawings are not drawn to scale, and some details are magnified and some details may be omitted for the purpose of clear expression. The shapes of various regions and layers shown in the drawings and the relative sizes and positional relationships between them are only exemplary, and may deviate in practice due to manufacturing tolerances or technical limitations, and those skilled in the art may design regions / layers with different shapes, sizes, and relative positions according to actual needs.

[0062] As one aspect of the present invention, a method for preparing hollow structure metal particles comprises the following steps:

[0063] 1) dissolving a soluble salt or soluble base in a good solvent to obtain a soluble salt or soluble base solution; dissolving a surface modifier in a poor solvent for the soluble salt or soluble base to obtain an anti-solvent for the corresponding soluble salt or soluble base;

[0064] 2) heating or freezing the soluble salt or soluble alkali solution and the anti-solvent respectively, and then stirring or ultrasonically mixing them in proportion to obtain a water-soluble salt or alkali template;

[0065] 3) dissolving the metal precursor and the surface modifier in a corresponding poor solvent of a soluble salt or a soluble base, and mixing them with a water-soluble salt or base template in proportion, stirring the reaction continuously, and washing by centrifugation to obtain hollow metal salt particles;

[0066] 4) dispersing the metal salt particles obtained in step 3) in a solvent, adding a reducing agent to carry out a reduction reaction under temperature-controlled stirring conditions to obtain a hollow metal particle suspension, centrifugally separating and washing to obtain hollow structure metal particles.

[0067] According to some embodiments of the present invention, in step 1), the soluble salt or soluble alkali is selected from one of the following substances: sodium chloride, sodium carbonate, sodium citrate, sodium sulfate, sodium nitrate, sodium hydroxide, potassium chloride, potassium carbonate, potassium citrate, potassium sulfate, potassium nitrate, potassium hydroxide. Because the soluble salt can be dissolved in water, the soluble salt can be removed by washing with water, while other types of salt water have poor solubility and cannot be removed by washing with water.

[0068] According to some embodiments of the present invention, in step 1), the good solvent for the soluble salt or soluble base is selected from one or more of the following substances: deionized water, glycerol, ethylene glycol, methanol. Other solvents are not suitable for dissolving soluble salts or are not miscible with the anti-solvent.

[0069] According to some embodiments of the present invention, in step 1), the surface modifier is selected from one or more of the following substances: hexadecyl trimethyl ammonium bromide, polyvinyl pyrrolidone, polyethylene glycol, sodium dodecyl sulfonate, sodium dodecyl sulfate, Tween 80, and silane coupling agent. The presence of surfactant reduces the oil-water interfacial tension, so that when the solvent and the anti-solvent are mixed, fine particles of soluble salt are precipitated, and at the same time, it plays a role of grafting on the surface of soluble salt particles. Selecting other surfactant raw materials cannot reduce the volume of precipitated particles and cannot be grafted to the surface of soluble salt particles.

[0070] According to certain embodiments of the present invention, in step 1), the poor solvent for the soluble salt or soluble base is selected from one or more of the following substances: ethanol, isopropanol, n-butanol, acetone, acetonitrile, tetrahydrofuran. Other poor solvents are not suitable for precipitating soluble salts, or are not miscible with the solvent.

[0071] According to some embodiments of the present invention, in step 1), the amount of the soluble salt or soluble alkali is 0.1wt% of the total mass of the good solvent to saturation; more preferably, the amount of the soluble salt or soluble alkali is 1wt% of the total mass of the good solvent to saturation. Outside this amount range, less amount will make it difficult to precipitate, and the obtained soluble salt particles will be too small; more amount will make it difficult to control the volume, and the obtained soluble salt particles will be too large.

[0072] According to some embodiments of the present invention, in step 1), the amount of the surface modifier is 0.1-2 wt% of the total mass of the poor solvent; more preferably, the amount of the surface modifier is 0.1-1 wt% of the total mass of the poor solvent. Outside this amount range, a smaller amount may result in an insignificant modification effect; a larger amount may result in uncontrollable precipitated particle size.

[0073] According to certain embodiments of the present invention, in step 2), the soluble salt or soluble alkali solution is heated to a temperature of 0-200° C. before being mixed with the antisolvent; more preferably, the soluble salt or soluble alkali solution is heated to a temperature of 50-100° C. before being mixed with the antisolvent. Outside this temperature range, the solubility of the soluble salt will decrease, and the temperature difference between the soluble salt solution and the antisolvent of the soluble salt is too large, which will make the two difficult to mix.

[0074] According to certain embodiments of the present invention, in step 2), the temperature of the anti-solvent before mixing is -20-60° C.; more preferably, the temperature of the anti-solvent before mixing is -10-25° C. Outside this temperature range, the yield of the obtained soluble salt particles will be too low and the volume will be too large. At the same time, the temperature difference between the soluble salt solution and the anti-solvent of the soluble salt is too large, which makes it difficult to mix the two.

[0075] According to some embodiments of the present invention, in step 2), the volume ratio of the soluble salt or soluble alkali solution to its anti-solvent is 1:5-1:200; more preferably, the volume ratio of the soluble salt or soluble alkali solution to its anti-solvent is 1:20-1:100. Outside this ratio range, a low ratio will reduce the yield; a high ratio will make the soluble salt particles too large and even difficult to precipitate.

[0076] According to some embodiments of the present invention, in step 2), the stirring rate is 300-2400 rpm; more preferably, the stirring rate is 600-1800 rpm. Outside this speed range, a low speed will increase the particle size and cause agglomeration; a high speed will cause the particles to be damaged and the morphology to become uncontrollable.

[0077] According to some embodiments of the present invention, in step 2), the ultrasonic power is 10-600 W; more preferably, the ultrasonic power is 100-600 W. Outside this power range, if the power is too low, the particle size will increase and agglomerate; if the power is too high, the particles will be damaged and the morphology will become uncontrollable.

[0078] According to some embodiments of the present invention, in step 2), the stirring or ultrasonic time is 1-30 minutes; more preferably, the stirring or ultrasonic time is 2-15 minutes. Outside this time range, if the stirring or ultrasonic time is too low, the particle size will increase and agglomerate; if the stirring or ultrasonic time is too high, the particles will be damaged and the morphology will become uncontrollable.

[0079] According to some embodiments of the present invention, in step 3), the metal precursor is selected from one or more of the following substances: silver nitrate, tetrachloroauric acid, copper sulfate, copper nitrate, ferric chloride, barium sulfate, barium chloride, cobalt chloride, and nickel chloride. The metal precursor is the main raw material for preparing hollow metal particles, and should react with soluble salts to form salt precipitation for in-situ reaction on the soluble salt template. Other metal precursors cannot react with soluble salts and are not soluble in poor solvents, which increases the difficulty of in-situ reaction.

[0080] According to some embodiments of the present invention, in step 3), the surfactant is selected from one or more of the following substances: polyvinyl pyrrolidone, polyethylene glycol, silane coupling agent, hexadecyltrimethylammonium bromide, Tween 80. The presence of the surfactant can activate the metal precursor, increase the solubility of the metal precursor in the poor solvent, and can also be used as a catalyst to catalyze the in-situ reaction to produce metal salts. Other surfactants cannot activate the metal precursor.

[0081] According to some embodiments of the present invention, in step 3), the amount of the metal precursor is 0.1-10wt% of the total mass of the poor solvent; more preferably, the amount of the metal precursor is 1-5wt% of the total mass of the poor solvent. Outside this amount range, there will not be enough metal precursor to react with the soluble salt; if it is too much, it cannot be completely dissolved in the poor solvent.

[0082] According to some embodiments of the present invention, in step 3), the amount of the surface modifier is 0.1-10wt% of the total mass of the poor solvent; more preferably, the amount of the surface modifier is 1-5wt% of the total mass of the poor solvent. Outside this amount range, a smaller amount may result in an insignificant modification effect; a larger amount may result in the precipitation of soluble salts during mixing.

[0083] According to some embodiments of the present invention, in step 3), the ratio of the metal precursor solution to the water-soluble template solution is 1:1-1:20; more preferably, the volume ratio of the metal precursor solution to the water-soluble salt or alkali template solution is 1:1-1:10. Outside this ratio range, if the ratio is too low, the metal salt and the soluble salt particles will not react completely; if the ratio is too high, the metal precursor will generate free metal salt particles.

[0084] According to some embodiments of the present invention, in step 3), the mixing and stirring time of the metal precursor solution and the water-soluble salt or alkali template solution is 1-96 hours; more preferably, the mixing and stirring time of the metal precursor solution and the water-soluble salt or alkali template solution is 24-72 hours. Outside this time range, if it is too short, the reaction will be incomplete; if it is too long, the soluble salt will gradually dissolve and generate free metal salt particles with the metal precursor.

[0085] According to some embodiments of the present invention, in step 3), the metal precursor solution and the water-soluble salt or alkali template solution are mixed and stirred at a temperature of -20-60°C; more preferably, the metal precursor solution and the water-soluble salt or alkali template solution are mixed and stirred at a temperature of -10-25°C. Outside this temperature range, if the temperature is too low, the reaction rate will be too slow; if the temperature is too high, the metal salt particles will grow too fast and have irregular morphology.

[0086] According to some embodiments of the present invention, in step 4), the solvent is selected from one or more of the following substances: ethanol, isopropanol, n-butanol, acetone, acetonitrile, tetrahydrofuran, deionized water, glycerol, ethylene glycol, methanol. The solvent provides a place for the reduction reaction. If other solvents are selected, the reducing agent cannot be dissolved, so that the reaction cannot proceed, or the solvent itself reacts with the reducing agent, which is not conducive to the reducing agent reducing the metal salt.

[0087] According to some embodiments of the present invention, in step 4), the reducing agent is selected from one or more of the following substances: hydrazine hydrate, sodium citrate, ascorbic acid, sodium borohydride, and ethylene glycol. The presence of the reducing agent can reduce the metal salt solution back to the metal element. When other reducing agents are selected, the reducing agent with poor reducing ability cannot reduce the metal salt. Changing to a stronger reducing agent will increase the reaction speed, resulting in uncontrollable reaction, damaged surface of the obtained metal particles, and uncontrollable morphology.

[0088] According to some embodiments of the present invention, in step 4), the reduction reaction time is 1 min-6 h; more preferably, the reduction reaction time is 10 min-1 h. Outside this time range, a shorter time will result in incomplete reaction; a longer time will result in reoxidation of the hollow metal particles.

[0089] According to some embodiments of the present invention, in step 4), the temperature of the temperature-controlled stirring is -20-60° C.; more preferably, the temperature of the temperature-controlled stirring is -10-25° C. Outside this temperature range, if the temperature is too low, the reaction rate will be too slow; if the temperature is too high, the surface of the hollow metal particles will be damaged and the morphology will be irregular.

[0090] Example 1

[0091] A method for preparing hollow structure silver particles comprises the following steps:

[0092] Dissolve 1.5g of sodium chloride in 5mL of deionized water to obtain a soluble salt solution, heat it to 30°C in a water bath and keep it constant; dissolve 1.5g of polyvinyl pyrrolidone in 200mL of anhydrous ethanol to obtain an anti-solvent for the soluble salt, cool it to 0°C through a low-temperature cooling circulation pump and keep it constant. Mix the two quickly under the action of a magnetic stirrer at a speed of 900rpm and continue stirring for 2min to obtain a hard template for the soluble salt;

[0093] 1.5 g of silver nitrate and 1.5 g of polyvinyl pyrrolidone were dissolved in 50 mL of anhydrous ethanol to obtain a metal precursor solution, which was added to the template solution and stirred for 24 h under magnetic stirring at 900 rpm. After stirring, the solution was centrifuged and washed three times with anhydrous ethanol and deionized water, respectively, to obtain hollow silver chloride particles;

[0094] The hollow silver chloride particles were dispersed in ethanol again, cooled to -5°C by a low-temperature cooling circulation pump and kept at a constant temperature. 0.1 g of sodium borohydride was added to the above dispersion under magnetic stirring at a speed of 900 rpm and stirred for 5 minutes to obtain a hollow silver particle dispersion; centrifuged and washed with anhydrous ethanol and deionized water for 3 times respectively to obtain hollow structure silver particles.

[0095] Figure 1 This is the scanning electron microscopy image of the hard template of the synthesized soluble salt, with a particle size of approximately 2.98μm.

[0096] Figure 2 Scanning electron micrograph of the synthesized hollow silver particles.

[0097] Example 2

[0098] A method for preparing hollow structure copper particles comprises the following steps:

[0099] Dissolve 1g of sodium carbonate in 5mL of propylene glycol to obtain a soluble salt solution, heat it to 180°C in an oil bath and keep it constant; dissolve 0.1g of Tween 80 in 300mL of n-butanol to obtain an anti-solvent for the soluble salt, cool it to -5°C through a low-temperature cooling circulation pump and keep it constant. Mix the two quickly under the action of ultrasonic crushing at an ultrasonic power of 200W and continue ultrasonication for 5 minutes to obtain a hard template for the soluble salt;

[0100] 2 g of copper sulfate and 0.1 g of Tween 80 were dissolved in 50 mL of n-butanol to obtain a metal precursor solution, which was added to the template solution and stirred for 48 h under magnetic stirring at 900 rpm. After stirring, the solution was centrifuged and washed three times with n-butanol, anhydrous ethanol and deionized water, respectively, to obtain hollow copper carbonate particles;

[0101] The hollow copper carbonate particles were dispersed in n-butanol again, cooled to -5°C by a low-temperature cooling circulation pump and kept at a constant temperature. 0.1 g of sodium borohydride was added to the above dispersion under magnetic stirring at a speed of 900 rpm and stirred for 5 minutes to obtain a hollow copper particle dispersion; centrifuged and washed with anhydrous ethanol and deionized water for 3 times respectively to obtain hollow structure copper particles.

[0102] Example 3

[0103] A method for preparing hollow structured iron particles comprises the following steps:

[0104] Dissolve 0.2g potassium carbonate in 5mL methanol to obtain a soluble salt solution, heat it to 25°C in a water bath and keep it constant; dissolve 1g silane coupling agent in 400mL tetrahydrofuran to obtain an anti-solvent for the soluble salt, cool it to -10°C by a low-temperature cooling circulation pump and keep it constant. Mix the two quickly under the action of magnetic stirring at a speed of 1200rpm and continue stirring for 10 minutes to obtain a hard template for the soluble salt;

[0105] Dissolve 0.5 g of ferric chloride and 0.5 g of silane coupling agent in 50 mL of tetrahydrofuran to obtain a metal precursor solution, add the solution to the template solution and continue stirring for 36 hours under magnetic stirring at 1200 rpm. After stirring, centrifuge the solution and wash it three times with tetrahydrofuran, anhydrous ethanol and deionized water respectively to obtain hollow iron carbonate particles;

[0106] The hollow iron carbonate particles were dispersed in tetrahydrofuran again, cooled to -5°C by a low-temperature cooling circulation pump and kept at a constant temperature. 0.1 g of hydrazine hydrate was added to the above dispersion under magnetic stirring at a speed of 1200 rpm and stirred for 5 minutes to obtain a hollow iron particle dispersion; centrifuged and washed with anhydrous ethanol and deionized water for 3 times respectively to obtain hollow structure iron particles.

[0107] Example 4

[0108] A method for preparing hollow structure nickel particles comprises the following steps:

[0109] Dissolve 0.5g of sodium hydroxide in 5mL of ethylene glycol to obtain a soluble salt solution, heat it to 60°C in a water bath and keep it constant; dissolve 2g of hexadecyltrimethylammonium bromide in 200mL of acetone to obtain an anti-solvent for the soluble salt, cool it to 0°C through a low-temperature cooling circulation pump and keep it constant. Mix the two quickly under the action of ultrasonic crushing at an ultrasonic power of 300W and continue ultrasonication for 15 minutes to obtain a hard template for the soluble salt;

[0110] Dissolve 1g nickel chloride and 1g hexadecyltrimethylammonium bromide in 50mL acetone to obtain a metal precursor solution, add the solution to the template solution and stir for 48h under magnetic stirring at 1200rpm. After stirring, centrifuge the solution and wash it three times with acetone, anhydrous ethanol and deionized water respectively to obtain hollow nickel hydroxide particles;

[0111] The hollow nickel hydroxide particles were dispersed in acetone again, cooled to -5°C by a low-temperature cooling circulation pump and kept at a constant temperature. 0.2 g of hydrazine hydrate was added to the above dispersion under magnetic stirring at a speed of 1200 rpm and stirred for 5 minutes to obtain a hollow nickel particle dispersion; centrifuged and washed with anhydrous ethanol and deionized water for 3 times respectively to obtain hollow structure nickel particles.

[0112] Example 5

[0113] A method for preparing hollow structure gold particles comprises the following steps:

[0114] Dissolve 4g potassium hydroxide in 5mL deionized water to obtain a soluble salt solution, heat it to 90°C in a water bath and keep it constant; dissolve 1g polyethylene glycol in 200mL acetonitrile to obtain an anti-solvent for the soluble salt, cool it to -5°C with a low-temperature cooling circulation pump and keep it constant. Mix the two quickly under the action of a magnetic stirrer at a speed of 900rpm and continue stirring for 15min to obtain a hard template for the soluble salt;

[0115] Dissolve 1g of tetrachloroauric acid and 1g of polyethylene glycol in 50mL of acetonitrile to obtain a metal precursor solution, add the solution to the template solution and stir for 24h under magnetic stirring at 900rpm. After stirring, centrifuge the solution and wash it three times with acetonitrile, anhydrous ethanol and deionized water respectively to obtain hollow gold hydroxide particles;

[0116] The hollow gold hydroxide particles were dispersed in acetonitrile, cooled to -10°C by a low-temperature cooling circulation pump and kept at a constant temperature. 0.2 g of ascorbic acid was added to the above dispersion under magnetic stirring at a speed of 900 rpm and stirred for 5 minutes to obtain a hollow gold particle dispersion; centrifuged and washed with anhydrous ethanol and deionized water for 3 times respectively to obtain hollow structure gold particles.

[0117] Example 6

[0118] A method for preparing hollow structure cobalt particles comprises the following steps:

[0119] Dissolve 1g of sodium sulfate in 5mL of ethylene glycol to obtain a soluble salt solution, heat it to 100°C in an oil bath and keep it constant; dissolve 1g of polyethylene glycol in 200mL of isopropanol to obtain an antisolvent for the soluble salt, cool it to -10°C and keep it constant by a low-temperature cooling circulation pump. Mix the two quickly under the action of a magnetic stirrer at a speed of 900rpm and continue stirring for 20min to obtain a hard template for the soluble salt;

[0120] Dissolve 1g of cobalt chloride and 1g of polyethylene glycol in 50mL of isopropanol to obtain a metal precursor solution, add the solution to the template solution and stir for 48h under magnetic stirring at 900rpm. After stirring, centrifuge the solution and wash it three times with isopropanol, anhydrous ethanol and deionized water respectively to obtain hollow cobalt sulfate particles;

[0121] The hollow cobalt sulfate particles were dispersed in isopropanol again, cooled to -5°C by a low-temperature cooling circulation pump and kept at a constant temperature. 0.2 g of sodium borohydride was added to the above dispersion under magnetic stirring at a speed of 900 rpm and stirred for 5 minutes to obtain a hollow cobalt particle dispersion. The mixture was centrifuged and washed with anhydrous ethanol and deionized water for 3 times respectively to obtain hollow structure cobalt particles.

[0122] Comparative Example 1

[0123] Example 1 was repeated except that the temperature of the anhydrous ethanol was 60° C. before mixing.

[0124] The soluble salt template prepared in this comparative example has a larger particle size and a wider particle size distribution. This is because when the mixing temperature is too high, the particles grow too fast and agglomerate between the particles, producing particles with larger particle sizes. The scanning electron microscope image of the soluble salt template prepared when the temperature of anhydrous ethanol is 60°C before mixing is as follows: Figure 3 As shown, the particle size is about 5.69 μm

[0125] Comparative Example 2

[0126] Example 1 was repeated, except that the mixing ratio of anhydrous ethanol to sodium chloride solution was 10:1.

[0127] The particle size of the soluble salt template in this comparative example is larger and the particle size distribution is wider. This is because when the anti-solvent ratio is too high, too many particles are precipitated, and at the same time, particles agglomerate with each other, producing particles with larger particle sizes. The scanning electron microscope image of the soluble salt template prepared when the mixing ratio of anhydrous ethanol and sodium chloride solution is 10:1 is shown in the figure. Figure 4 As shown, the particle size is about 3.69 μm.

[0128] Comparative Example 3

[0129] Example 1 was repeated, except that the mixing ratio of anhydrous ethanol to sodium chloride solution was 120:1.

[0130] The soluble salt template of this comparative example is seriously damaged, with a large particle size and a wide particle size distribution. This is because when the anti-solvent ratio is too low, too many particles are nucleated, many particles are not fully grown, and the surface is damaged. The scanning electron microscope image of the soluble salt template prepared when the mixing ratio of anhydrous ethanol and sodium chloride solution is 120:1 is as follows Figure 5 As shown, the particle size is about 6.23 μm.

[0131] Comparative Example 4

[0132] Repeat Example 1: the only difference is that the consumption of sodium chloride is 0.375g.

[0133] The soluble salt template of this comparative example is seriously damaged, with a large particle size and a wide particle size distribution. This is because when the amount of sodium chloride is too low, too many particles are nucleated, many particles are not fully grown, and the surface is damaged. The scanning electron microscope image of the soluble salt template prepared when the amount of sodium chloride is 0.375g is as follows Figure 6 As shown, the particle size is about 5.28 μm

[0134] Comparative Example 5

[0135] Example 1 was repeated, except that the stirring time after the metal precursor and the template were mixed was 1 h.

[0136] The surface of the hollow silver particles in this comparative example is severely damaged. This is because the mixing time is too short, resulting in incomplete growth of silver chloride and failure to form a silver nitrate shell at some locations of the template, which results in severe surface damage to the hollow silver particles. The scanning electron microscope image of the hollow silver particles prepared when the metal precursor and the template are mixed and stirred for 1 hour is shown in FIG. Figure 7 shown.

[0137] Comparative Example 6

[0138] Example 1 was repeated except that the hollow silver chloride particles were redispersed in deionized water instead of ethanol.

[0139] The surface of the hollow silver particles in this comparative example is severely damaged. This is because the reducing agent is highly active in water and the reaction rate cannot be accurately controlled, resulting in the surface of the hollow silver particles being damaged. The scanning electron microscope image of the hollow silver particles prepared by re-dispersing the hollow silver chloride particles in deionized water is shown in FIG. Figure 8 shown.

[0140] Comparative Example 7

[0141] Example 1 was repeated except that the solution temperature was 30°C during the reduction reaction.

[0142] The surface of the hollow silver particles in this comparative example is severely damaged. This is because the reaction is violent at a high temperature and the reaction rate cannot be accurately controlled, resulting in the surface of the hollow silver particles being damaged. The scanning electron microscope image of the hollow silver particles prepared when the solution temperature is 30°C during the reduction reaction is as follows: Fig. 9 shown.

[0143] Obviously, the above embodiments of the present invention are merely examples for clearly explaining the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for preparing hollow structure metal particles, characterized in that: The steps include: 1) dissolving a soluble salt or soluble base in a good solvent to obtain a soluble salt or soluble base solution; dissolving a surface modifier in a poor solvent for the soluble salt or soluble base to obtain an anti-solvent for the corresponding soluble salt or soluble base; 2) heating or freezing the soluble salt or soluble alkali solution and the anti-solvent respectively, and then stirring or ultrasonically mixing them in proportion to obtain a water-soluble salt or alkali template; 3) dissolving the metal precursor and the surface modifier in a corresponding poor solvent of a soluble salt or a soluble base, and mixing them with a water-soluble salt or base template in proportion, stirring the reaction continuously, and washing by centrifugation to obtain hollow metal salt particles; 4) dispersing the metal salt particles obtained in step 3) in a solvent, adding a reducing agent to carry out a reduction reaction under temperature-controlled stirring conditions to obtain a hollow metal particle suspension, centrifugally separating and washing to obtain hollow structure metal particles.

2. The method for preparing the hollow structure metal particles according to claim 1, characterized in that: In step 1), the soluble salt or soluble base is selected from one of the following substances: sodium chloride, sodium carbonate, sodium citrate, sodium sulfate, sodium nitrate, sodium hydroxide, potassium chloride, potassium carbonate, potassium citrate, potassium sulfate, potassium nitrate, potassium hydroxide.

3. The method for preparing the hollow structure metal particles according to claim 1, characterized in that: In step 1), the good solvent for the soluble salt or soluble base is selected from one or more of the following substances: deionized water, glycerol, ethylene glycol, and methanol.

4. The method for preparing hollow structure metal particles according to claim 1, characterized in that: In step 1), the surface modifier is selected from one or more of the following substances: hexadecyltrimethylammonium bromide, polyvinyl pyrrolidone, polyethylene glycol, sodium dodecyl sulfonate, sodium dodecyl sulfate, Tween 80, and silane coupling agent.

5. The method for preparing hollow structure metal particles according to claim 1, characterized in that: In step 1), the poor solvent for the soluble salt or soluble base is selected from one or more of the following substances: ethanol, isopropanol, n-butanol, acetone, acetonitrile, and tetrahydrofuran.

6. The method for preparing hollow structure metal particles according to claim 1, characterized in that: In step 1), the amount of the soluble salt or soluble base is 0.1wt% to saturation of the total mass of the good solvent; more preferably, the amount of the soluble salt or soluble base is 1wt% to saturation of the total mass of the good solvent.

7. The method for preparing hollow structure metal particles according to claim 1, characterized in that: In step 1), the amount of the surface modifier is 0.1-2 wt % of the total mass of the poor solvent; more preferably, the amount of the surface modifier is 0.1-1 wt % of the total mass of the poor solvent.

8. The method for preparing hollow structure metal particles according to claim 1, characterized in that: In step 2), the soluble salt or soluble alkali solution is heated to a temperature of 0-200° C. before being mixed with the anti-solvent; more preferably, the soluble salt or soluble alkali solution is heated to a temperature of 50-100° C. before being mixed with the anti-solvent; Preferably, in step 2), the temperature of the anti-solvent before mixing is -20-60°C; more preferably, the temperature of the anti-solvent before mixing is -10-25°C; Preferably, in step 2), the volume ratio of the soluble salt or soluble alkali solution to its anti-solvent is 1:5-1:200; more preferably, the volume ratio of the soluble salt or soluble alkali solution to its anti-solvent is 1:20-1:100; Preferably, in step 2), the stirring rate is 300-2400 rpm; more preferably, the stirring rate is 600-1800 rpm; Preferably, in step 2), the ultrasonic power is 10-600W; more preferably, the ultrasonic power is 100-600W; Preferably, in step 2), the stirring or ultrasonic time is 1-30 min; more preferably, the stirring or ultrasonic time is 2-15 min.

9. The method for preparing hollow structure metal particles according to claim 1, characterized in that: In step 3), the metal precursor is selected from one or more of the following substances: silver nitrate, tetrachloroauric acid, copper sulfate, copper nitrate, ferric chloride, barium sulfate, barium chloride, cobalt chloride, nickel chloride; Preferably, in step 3), the surfactant is selected from one or more of the following substances: polyvinyl pyrrolidone, polyethylene glycol, silane coupling agent, hexadecyltrimethylammonium bromide, Tween 80; Preferably, in step 3), the amount of the metal precursor is 0.1-10wt% of the total mass of the poor solvent; more preferably, the amount of the metal precursor is 1-5wt% of the total mass of the poor solvent; Preferably, in step 3), the amount of the surface modifier is 0.1-10wt% of the total mass of the poor solvent; more preferably, the amount of the surface modifier is 1-5wt% of the total mass of the poor solvent; Preferably, in step 3), the ratio of the metal precursor solution to the water-soluble template solution is 1:1-1:20; more preferably, the volume ratio of the metal precursor solution to the water-soluble salt or base template solution is 1:1-1:10; Preferably, in step 3), the mixing and stirring time of the metal precursor solution and the water-soluble salt or alkali template solution is 1-96 hours; more preferably, the mixing and stirring time of the metal precursor solution and the water-soluble salt or alkali template solution is 24-72 hours; Preferably, in step 3), the metal precursor solution and the water-soluble salt or alkali template solution are mixed and stirred at a temperature of -20-60°C; more preferably, the metal precursor solution and the water-soluble salt or alkali template solution are mixed and stirred at a temperature of -10-25°C.

10. The method for preparing hollow structure metal particles according to claim 1, characterized in that: In step 4), the solvent is selected from one or more of the following substances: ethanol, isopropanol, n-butanol, acetone, acetonitrile, tetrahydrofuran, deionized water, glycerol, ethylene glycol, methanol; Preferably, in step 4), the reducing agent is selected from one or more of the following substances: hydrazine hydrate, sodium citrate, ascorbic acid, sodium borohydride, ethylene glycol; Preferably, in step 4), the reduction reaction time is 1 min-6 h; more preferably, the reduction reaction time is 10 min-1 h; Preferably, in step 4), the temperature of the temperature-controlled stirring is -20-60°C; more preferably, the temperature of the temperature-controlled stirring is -10-25°C.

Citation Information

Patent Citations

  • Preparation method for micron order superfine sodium chloride

    CN101565190A

  • Preparation method for hollow nano metal

    CN103231069A

  • Water-soluble sodium halide micro-particles, and preparation method and application thereof

    CN103318922A

  • Hollow spherical precious metal nanometer material preparation method

    CN104259473A

  • Method for preparing hollow cubic micro-nano metal

    CN104308172A